Nazwy "skrzypu <equisetum>" w?dialekcie śląskim = The names of "skrzyp <equisetum>" in the Silesian dialect - Wyderka, Bogusław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In Silesia, as well as in other Polish regions, there is a considerable number of names for skrzyp "Equisetum". According to the "Atlas językowy Śląska" [Liguistic Atlas of Silesia] by A. Zaręba, the names for skrzyp build quite clear geographical zones. To the north of the isolexis of Chocianowice (Kluczbork district) and Stare Budkowice (Opole district) appear variants of the lexeme "kostka". In the central Silesia to Chełm Śląski (Tychy district), Bełk (Rybnik district), Rogów (Wodzisław district) occurs "przęcka". However, below the line in the southern Silesia, a mixed zone with variants of the names "kocur", "chwost" and "kocycoł" exists.
Keywords: dialekt śląski; leksyka; nazwy skrzypu "Equisetum"; Silesian dialect; lexis; names of skrzyp "Equisetum"